PENATAAN LEMBAGA PENYIARAN KOMUNITAS DALAM AKVITAS PENYIARAN DI INDONESIA - Ahmad Budiman (Jurnal Politica, 2014)
Community Broadcasting Agency (LPK) is one of several agencies of broadcasting existing in Indonesia today. Its activity is not commercial in nature, and it is created by certain groups of community. Its loyal users and limited frequency capacity cause its program focus only on issues of information, education and culture of its community. Some operational problem facing by the LPK are difficulty in obtaining broadcasting license, as well as limited budget provided by the state to support its activity, and also the quality of program. The new approach is intended to maximize the functions of this community broadcasting for public. Away from this, the new approach is perceived necessary for the reasons of improving its legal basis, source of budget, the availability of channels, its covering capacity, and program quality.